Enhancing extracurricular sports activities for students of Thai Nguyen University of Technology - Nhan, Duong (IJRDO- Journal of Educational Research, 2020)
The writing analyzes the concept, forms and benefits of extracurricular sports activities for students in general and students of Thai Nguyen University of Technology (TNUT) in particular. From these theoretical bases, the author analyzes the achieved results and some limitations and difficulties; at the same time, proposes some measures to enhance extracurricular sports activities for students of TNUT.